Gregg College Keyboarding & Document Processing (GDP), Lessons 1-60, Student Text (Gregg College Keyboarding & Document Processing for Windows) (Paperback) - Ober Scot (McGraw Hill/Irwin, 2002)
The ninth edition of this industry leader provides a highly flexible format on CD-ROM and 3.5" disks that will work with your current computer setup. New content reflecting changing technology and workplace needs is presented in four-color, side-spiral bound texts. Multiple software enhancements and a flexible Web-Based Instructor Management Web site support the program's strong content. The software, textbook, and manuals are integrated to provide students with a total learning experience. Instructors will appreciate the flexibility of using a program that can be successfully implemented in a variety of classroom environments.